The algebra of happiness : notes on the pursuit of success, love, and meaning - Galloway, Scott, 1964- (Portfolio, Penguin, 2019)
"From the New York Times bestselling author of The Four, Scott Galloway, a provocative book of hard-won wisdom for achieving a fulfilling career and life, based on his viral video of the same name. Scott Galloway teaches brand strategy at NYU's Stern School of Business, but often his class veers to life strategy. His students are smart and hardworking, but they struggle with life's biggest questions, just like the rest of us. What's the formula for a life well lived? How can you have a meaningful career, not just a lucrative one? Is work/life balance really possible? What does it take to make a long-term relationship succeed? Galloway explores these and many other questions in the take-no-prisoners style that has made him a sought-after commentator and YouTube star. For example... If (Money In) - (Money Out) > 0, you're rich. The definition of "rich" is income greater than your burn rate. My dad and his wife receive about $50K/year and spend $40K. They are rich. I have friends who earn more than $1 million, but with several children in private schools, an ex-wife, a home in the Hamptons, and the lifestyle of a master of the universe, they spend nearly all of it. They are poor. Compound interest = the key to relationships. Most of us know how compound interest works with money, but don't recognize its power in other spheres. Make small investments in the people you care about, every day. Take a ton of pictures, text your friends stupid things, check in with old friends, express admiration to coworkers, and tell your loved ones that you love them. The payoff is small, until it becomes immense. Serendipity = a function of courage. My willingness to endure rejection from universities, peers, investors, and women has been hugely rewarding. Asking a VC for money is nothing compared to approaching a woman midday in a beach chair, sitting with another woman and a guy, and opening. Nothing wonderful will happen without taking a risk and subjecting yourself to rejection. Cool vacation > Cool car. Studies show people overestimate the happiness that things will bring them, and underestimate the long-term positive effect of experiences. Invest in experiences over things. Drive a Hyundai, and take your spouse to Australia. The Algebra of Happiness is perfect for any graduate, or for anyone who feels adrift"--